Determinan profitabilitas perbankan syariah di Indonesia: peran moderasi non performing financing - Malik, Muhammad Abdul; Anwar, Saiful (Nur Science Institute, 2021)
This study aims to examine the effect of profit sharing, BOPO and financing on profitability with non-performing financing (NPF) as a moderating variable. This study uses linear regression analysis of panel data on 11 Islamic Commercial Banks (BUS) for the 2015-2019 period in Indonesia. The results of this study indicate that profit sharing and financing have a positive effect, BOPO has a negative effect on the profitability of Islamic banking in Indonesia. The relationship between profit sharing and financing in Islamic banking is moderated by non-performing financing, but not with the relationship for financing and operating income (BOPO) which is not able to moderate by non-performing financing. This research contributes to Islamic banking in Indonesia in order to make effective financing with results sharing and operational cost efficiency in operating income (BOPO) so that performance can improve financial performance.